Optimization and Preparation of Polysaccharide–Protamine Microspheres with Enhanced Hemostatic and Antibacterial Properties for Wound Healing - Danling Mei; Feifan Cheng; Yifan Li; Suzhen Zhang; Xueqin Zhao; Yanyan Zhao (Marine Drugs)
This study employs layer-by-layer self-assembly technology to develop novel antibacterial hemostatic microspheres to tackle significant blood loss and related complications resulting from accidents, surgeries, and natural disasters. By measuring the zeta potential and particle size of protamine, carboxymethyl starch (CMS), and hydroxypropyl trimethyl ammonium chloride chitosan (HACC), the optimal assembly conditions were determined. The optimal pH for the monolayer assembly is 3.0, with a CMS concentration of 3 mg/mL and a mass ratio of 1:4 between protamine and CMS, and the assembly process lasts for 2 h. The optimal assembly conditions for the bilayer assembly are a pH of 4.0, an HACC concentration of 1 mg/mL, and a mass ratio of the one-layer assembly to HACC of 1:2. The performance of the assembled microspheres was analyzed via antibacterial and coagulation experiments, revealing excellent antibacterial and coagulation effects, with inhibition rates against Escherichia coli and Bacillus subtilis both exceeding 99%, and a coagulation index of 0%. Additionally, the bilayer assembled microspheres also exhibited strong adsorption capacity and good biocompatibility. In summary, this study provides important scientific evidence for the development of new hemostatic materials, demonstrating significant clinical application potential.